High-throughput profiling of posttranslational modification enzymes by phage display. (July 2007) - Yen, Michelle; Yin, Jun
Phage display has been used as a high-throughput platform for identifying proteins or peptides with desired binding or catalytic activities from a complex proteome. Recently, phage display has been applied to profile the catalytic activities of posttranslational modification (PTM) enzymes. Here, we highlight recent work elucidation the downstream targets of PTM enzymes by phage display, including the genome-wide profiling of biosynthetic enzymes subject to phosphopantetheinyl transferase (PPTase) modification.